American Society Viewed from Youths’ Lens: A Study on Bob Dylan’s “A Hard Rain’s a-Gonna Fall” - Fauzan Rodi; Rahmawan Jatmiko (Universitas Gadjah Mada, 2018)
This study examines the lyric of a famous song entitled A Hard Rains a-Gonna Fall composed by American folk musician, Bob Dylan. The objective of this study is to analyze the perspective of the baby-boomer generation, which remarkably differs from that of the older generations in terms of their attitude on certain issues such as war, social injustice, racism and equality in the 1960s America. All of these are reflected in the lyric of the song and also in the sociological and historical facts around the time when the work was created. The approach of sociological literature is employed in this study, which is chosen for the analysis to start from the assumption that the meaning of the lyrics is seen as the reflection of what happens in the society. This is also to reconfirm that a literary work can be used as a means of analyzing a period of time and, therefore, giving insights as to how the general public think about it.